The Catholic Church and Portugal in Africa - Pedro Ramos Brandao (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The way Catholic Church implanted itself in Africa, and particularly in Portuguese colonial Africa, during the first half of the 20th century. The issue of the Organic Statute of Portuguese Catholic Missions in Africa. The orientation of the missionary policy and its integration in 1933 Constitution. The Foreign Missionaries in the Portuguese Missions and their impact on the criticism to Colonization. The Missionary Statute. The issue of Beira's Bishop.